(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
In most of the shrimp farming ponds deterioration of water quality, pond bottom condition, incidence of toxic gases like NH3, NO2, H2S etc. and occurrence of disease appear generally after 60 days of farming onwards. As a remedial measure, application of probiotics as a biotechnological tool for bioremediation has been suggested for shrimp farm located in a Srijang village near Chandipur area of coastal Balasore, Orissa, (India) and was found to be effective in controlling and reducing of pathogenic vibrio population and toxic gases. Key words: Probiotics; Shrimp; Aquaculture; Bioremediation; Diseases; Toxic gases DOI: http://dx.doi.org/10.3329/jbas.v35i2.9430 JBAS 2011; 35(2): 237-240